Sub-4-optical-cycle, 340 MW peak power, high stability mid-IR source at 160 kHz. (September 2015) - Baudisch, M; Pires, H; Ishizuki, H; Taira, T; Hemmer, M; Biegert, J
Abstract We present the state of the art of our development of a unique high average power mid-infrared (IR) optical parametric chirped pulse amplification (OPCPA) source. The system delivers passively carrier-envelope phase (CEP)-stable optical pulses with 20 μJ of energy at 3.05 μm center wavelength and a duration of 55 fs (5.4 optical cycles). Implementing an all-solid-state self-compression scheme, we produce 38 fs (3.7 optical cycles) duration pulses at 13 μJ energy and 32 fs (2.9 optical cycles) duration pulses at 2 μJ energy. In addition, an intrinsically synchronized near-IR output delivering optical pulses with 15 μJ energy, 96 fs duration at 1.62 μm center wavelength is derived from the system—this additional output can be used for multi-color experiments or impulsive alignment. The excellent long-term stability of less than 1% root mean square (rms) power fluctuations over 12.5 h at 160 kHz makes this source an ideal driver for nonlinear optics experiments, in particular mid-IR-driven strong-field physics and attoscience.